If you give a mouse a cookie - Numeroff, Laura Joffe; Bond, Felicia (New York : Harper & Row, 1985)
A young boy, having given a cookie to a bossy mouse, is run ragged by the energetic rodent's subsequent requests.
Sequel: If you give a moose a muffin.
Book Links (A.L.A.).
School Library Journal.
Wilson's Children.
1.8
K-3
Keywords: Mice -- Fiction; Mice -- Fiction